Benefits of the prone position in patients with non-intubated COVID-19 (Research, Society and Development, 2021)
The aim of the study was to highlight the benefits of the prone position in patients with unintubated COVID-19. This is an integrative literature review, using the keywords "prone position" and "coronavirus" not "respiration, artificial", using the PubMed databases, Google Scholar, the Virtual Health Library (VHL), Latin Literature -American and Caribbean Health Sciences (LILACS). After applying the inclusion and exclusion criteria, the PRISMA flowchart was used to elucidate the selection of articles and a table showing the results that make up the review. The prone position in patients affected by SARS-COV-2 on non-invasive ventilation has mainly brought about a reduction in respiratory effort and it has been reported that it has led to a lower incidence of intubation. Furthermore, it can improve pulmonary homogeneity, pulmonary redistribution, lung compliance, the proportion of recruitment for infiltration and lung recruitment. In conclusion, the prone position provides several benefits for patients not intubated with COVID-19, providing improved saturation and reduced mortality, in addition to preventing intubation.